The Kintsugi Art of Care: Unraveling Consent in Ethical Non-Monogamies. (December 2019) - Gusmano, Beatrice
Making a contribution to the sociology of intimacy, this article aims to present how lesbian, gay, bisexual, transsexual, and queer people live their ethical non-monogamous relationships in Italy. Giving great space to the concept of consent through the literature on the ethics of care, I will refer to different conceptualizations of critical consent given by feminist and BDSM communities, spaces in which ethics is based on unveiling power structures through the focus on consent. In fact, the centrality of the collective dimension in embracing ethical non-monogamies appears fundamental, challenging the self-help – and neoliberal – literature according to which polyamory is just a personal choice. Afterwards, I will deepen the concept of care, developing it through its means of communication, attentiveness, responsibility, and responsiveness within relationships. Presented this way, care recognizes us all as interdependent: at the same time, care-givers and care-receivers. I suggest that this interdependency is symbolized by the kintsugi, the Japanese art of repairing broken pottery with a mix of golden powder, a representation of the manifold matrix of care, composed of care-giving, care-receiving, and care for oneself.